Aerosol Deposition of Ba0.8Sr0.2TiO3 Thin Films - Brankovic, Z.; Brankovic, G.; Tucic, A.; Radojkovic, A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Int Inst Science Sintering (i I S S), 2009)
In this work we optimized conditions for aerosol deposition of homogeneous, nano-grained, smooth Ba0.8Sr0.2TiO3 thin films. Investigation involved optimization of deposition parameters, namely deposition time and temperature for different substrates. Solutions were prepared from titanium isopropoxide, strontium acetate and barium acetate. Films were deposited on Si (1 0 0) or Si covered by platinum (Pt (1 1 1) /Ti/SiO2/Si). Investigation showed that the best films were obtained at substrate temperature of 85 degrees C. After deposition films were slowly heated up to 650 degrees C, annealed for 30 min, and slowly cooled. Grain size of BST films deposited on Si substrate were in the range 40-70 nm, depending on deposition conditions, while the same films deposited on Pt substrates showed mean grain size in the range 35-50 nm. Films deposited under optimal conditions were very homogeneous, crack-free, and smooth with rms roughness lower than 4 nm for both substrates.
Keywords: Thin films; Aerosol deposition; Barium Strontium Titanate; Roughness